Towards clinical implementation of ultrafast combined kV-MV CBCT for IGRT of lung cancer: evaluation of registration accuracy based on phantom study - Arns, Anna Maria; Blessing, Manuel; Fleckenstein, Jens; Stsepankou, Dzmitry; Boda-Heggemann, Judit; Simeonova-Chergou, Anna; Hesser, Jürgen; Lohr, Frank; Wenz, Frederik; Wertz, Hansjörg (Strahlentherapie und Onkologie, 2016)
Purpose: Combined kV-MV cone-beam CT (CBCT) is a promising approach to accelerate imaging for patients with lung tumors treated with deep inspiration breath-hold. During a single breath-hold (15 s), a 3D kV-MV CBCT can be acquired, thus minimizing motion artifacts and increasing patient comfort. Prior to clinical implementation, positioning accuracy was evaluated and compared to clinically established imaging techniques. Methods and materials: An inhomogeneous thorax phantom with four tumor-mimicking inlays was imaged in 10 predefined positions and registered to a planning CT. Novel kV-MV CBCT imaging (90° arc) was compared to clinically established kV-chest CBCT (360°) as well as nonclinical kV-CBCT and low-dose MV-CBCT (each 180°). Manual registration, automatic registration provided by the manufacturer and an additional in-house developed manufacturer-independent framework based on the MATLAB registration toolkit were applied. Results: Systematic setup error was reduced to 0.05 mm by high-precision phantom positioning with optical tracking. Stochastic mean displacement errors were 0.5 ± 0.3 mm in right-left, 0.4 ± 0.4 mm in anteroposterior and 0.0 ± 0.4 mm in craniocaudal directions for kV-MV CBCT with manual registration (maximum errors of no more than 1.4 mm). Clinical kV-chest CBCT resulted in mean errors of 0.2 mm (other modalities: 0.4-0.8 mm). Similar results were achieved with both automatic registration methods. Conclusion: The comparison study of repositioning accuracy between novel kV-MV CBCT and clinically established volume imaging demonstrated that registration accuracy is maintained below 1 mm. Since imaging time is reduced to one breath-hold, kV-MV CBCT is ideal for image guidance, e.g., in lung stereotactic ablative radiotherapy.
Gesehen am 29.04.2019